1995
DOI: 10.1254/jjp.67.321
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of Capsaicin-Sensitive Sensory Neurons in Rat Stomachs on Chronic Treatment with Sodium Taurocholate

Abstract: ABSTRACT-We examined the effects of chronic treatment with 10 mM sodium taurocholate (TC) on gastric functions, capsaicin-sensitive afferent neurons and the gastric mucosa in male rats. Stomachs were mounted in Lucite chambers, and then the transmucosal potential difference (PD), luminal pH and gastric mucosal blood flow (GMBF) in response to TC or capsaicin was determined. In normal animals, 10 mM TC caused a reduction in PD, and increases in luminal pH and GMBF. Capsaicin (1 mg/ml) produced an apparent incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Previously, it has been reported that gastric infl ammation associated with alkaline refl ux was partly associated with desensitization of capsaicin-sensitive afferent neurons by bile. 35 Additionally, capsaicin, a component of red pepper, has been found to be effi cacious in patients with functional dyspepsia, probably through a desensitization of afferent neurons. 36 In one study, evaluation of jejunal specimens of patients with irritable bowel syndrome showed preganglionic infl ammation and neuronal degeneration in Histopathology scores…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been reported that gastric infl ammation associated with alkaline refl ux was partly associated with desensitization of capsaicin-sensitive afferent neurons by bile. 35 Additionally, capsaicin, a component of red pepper, has been found to be effi cacious in patients with functional dyspepsia, probably through a desensitization of afferent neurons. 36 In one study, evaluation of jejunal specimens of patients with irritable bowel syndrome showed preganglionic infl ammation and neuronal degeneration in Histopathology scores…”
Section: Discussionmentioning
confidence: 99%
“…Investigations have been made using invivo stomach, 21 stomach mounted in ex vivo chamber preparations, [22][23][24][25][26][27][28][29][30]32,35,120 stomach chambered with the blood supply intact, 33 glandular stomach of anesthetized rats chambered between two plastic rings, 34 perfused duodenum of anesthetized rats or duodenal loop of rats 23,42 and conscious dogs with duodenal loops and Heidenhain pouches. 44 The administration of capsaicin, various noxious agents, and the assay of certain gastric constituents have been made using rats, dogs, and cats with gastric fistula and gastric cannula, 45−49 anesthetized rats and chronically implanted gastric and duodenal cannula, 50,51,189 awake male beagle dogs with a chronic intra cerebro ventricular (i.c.v) cannula and gastric fistula 52 and anesthetized rats fasted overnight with acutely cannulated cisterna magna.…”
Section: Methodsmentioning
confidence: 99%
“…86,93 The length and surface area of injury has been measured by planimetry 31,46,89 and by computerized image analysis. 93 The transmucosal potential difference (pd) followed as an indication of surface epithelial injury 24,27,29,34,38,42,94 has been measured by mounting the tissue in an Ussing chamber perfusion system. The undamaged mucosa maintained a pd of about −64 mv in both control and after calcitonin gene-related peptide (CGRP) treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We reported that chronic administration of 10 mM sodium taurocholate (TC) to rats for > 4 weeks apparently desensitized capsaicin-sensitive afferent neurons (capsaicin-sensitive neurons) in the gastric mucosa, as evidenced by the reduced release of calcitonin gene-related peptide (CGRP) (1). Since chronic treatment with TC induces erosive or atrophic gastritis (2, 3), we proposed that the desensitization of capsaicin-sensitive neurons is one of the causal factors for such pathologic changes.…”
mentioning
confidence: 99%